Primary systemic vasculitis - Maj, Joanna; Reich, Adam; Baran, Eugeniusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
The term primary systemic vasculitis describes a wide spectrum of systemic diseases of unknown etiology with different morphology, pathogenesis and clinical manifestations, but with one common feature, that is, the damage of vessels. Following diseases are considered as primary systemic vasculitis: cutaneous leukocytoclastic angiitis, Henoch-Schönlein purpura, cryoglobulinemic vasculitis, microscopic vasculitis, Wegener’s granulomatosis, Churg-Strauss syndrome, Kawasaki disease, polyarteritis nodosa, giant-cell arteritis and Takayasu disease. The most important factor responsible for the vessel damage is the deposition of antigen-antibody complexes within the vessel walls. The deposits activate complement and neutrophils, which impair blood vessels. The most often used treatment modalities consist of sulphones, colchicine, corticosteroids, cyclosporine, cyclophosphamide and azathioprine, and recently also new drugs, like etanercept, infliximab or rituximab are even employed.